Innovation Management in Malaysian Organisations a Comparison Between Japanese and Malaysian Organisations - Cheong , Adeline Yu Nah (1998)
This study was conducted out of the need to examine the innovation management in Malaysian organisations (a comparison between the Japanese and the Malaysian organisations). The innovativeness of twelve organisations, where six are Japanese and the other six are Malaysian, was compared using the creative climate questionnaire (CCQ) developed by Ekvall et. al. (1983). Besides that, various aspects of innovation in the Japanese and the Malaysian organisations such as the technological and process innovation, product innovation, the cultural and financial performance of the organisations are being compared. Data for this research was obtained through interviews, the use of validated questionnaire, and the secondary sources. The results from this study showed that both the Malaysian and Japanese organisations are innovative. However, the Japanese organisations have a more creative climate, emphasize more on technological, process and product innovations compared to the Malaysian organisations. The results revealed that the culture of Japanese organisations is different from the culture of Malaysian organisations in some aspects such as life long employment, seniority system and status equalization. Besides that, the Japanese organisations also have better financial perfonnance than the Malaysian organisations. On the whole, the overall results from this study showed that Japanese organisations are more innovative than Malaysian organisations. This research contributes to a better understanding of the innovation practices in the Malaysian and Japanese organisations. The study may enable Malaysian organisations to adopt some of the relevant innovations in Japanese organisations. This study may also help to improve the Malaysian managers' ability to prescribe adequate strategies and tactics that can enhance the success of innovation practices in the Malaysian organisations.